High Temperature Conductive Stability of Indium Tin Oxide Films - Li, Haiou; Guo, Lei; Liu, Xingpeng; Sun, Tangyou; Li, Qi; Zhang, Fabi; Xiao, Gongli; Fu, Tao; Chen, Yonghe (Frontiers in Materials, 2020)
Indium tin oxide (ITO) has been studied for applications at normal high temperatures, below 600°C, due to its excellent electrical characteristics. In an attempt to further match the needs of electronics for use in extremely harsh environments, the changes in the conductive properties of ITO films and their mechanism were investigated at special high-temperatures above 1,000°C. ITO films were prepared by pulsed laser deposition (PLD) onto lanthanum gallium silicate (LGS) substrates. Furthermore, the as-deposited samples were annealed with different temperature-time treatments, and we investigated the effects of annealing on the electrical, structure, surface morphology and chemical properties of the ITO films by X-ray diffraction analysis, scanning electron microscopy (SEM), resistance measurements, and X-ray photoelectron spectroscopy (XPS). The experimental results showed that the decreased resistance of the ITO films was mainly attributed to the increase in the crystalline size and the increased amount of Sn4+ ions during the heating period (0–1,000°C). Generally, the ITO films showed stable electrical properties when they were heated at 1,000°C for at least 2.5 h. As expected, the ITO films that remained steady above 1,000°C have potential applications as electrodes working in special high-temperature environments.